Current landscape of cystic fibrosis gene therapy - Plasschaert, Lindsey W.; MacDonald, Kelvin D.; Moffit, Jeffrey S. (Frontiers in Pharmacology, 2024)
Cystic fibrosis is a life-threatening disease that is caused by mutations in CFTR, a gene which encodes an ion channel that supports proper function of several epithelial tissues, most critically the lung. Without CFTR, airway barrier mechanisms are impaired, allowing for chronic, recurrent infections that result in airway remodeling and deterioration of lung structure and function. Small molecule modulators can rescue existing, defective CFTR protein; however, they still leave a subset of people with CF with no current disease modifying treatments, aside from lung transplantation. Gene therapy directed to the lung is a promising strategy to modify CF disease in the organ most associated with morbidity and mortality. It is accomplished through delivery of a CFTR transgene with an airway permissive vector. Despite more than three decades of research in this area, a lung directed gene therapy has yet to be realized. There is hope that with improved delivery vectors, sufficient transduction of airway cells can achieve therapeutic levels of functional CFTR. In order to do this, preclinical programs need to meet a certain level of CFTR protein expression in vitro and in vivo through improved transduction, particularly in relevant airway cell types. Furthermore, clinical programs must be designed with sensitive methods to detect CFTR expression and function as well as methods to measure meaningful endpoints for lung structure, function and disease. Here, we discuss the current understanding of how much and where CFTR needs to be expressed, the most advanced vectors for CFTR delivery and clinical considerations for detecting CFTR protein and function in different patient subsets.